PENGARUH PENERAPAN PEMBELAJARAN AKTIF TIPE HOLLYWOOD SQUARES MENGGUNAKAN LKS TERHADAP HASIL BELAJAR GEOGRAFI SISWA KELAS XI IPS SMAN I SUTERA KABUPATEN PESISIR SELATAN - Fitri Rahmadani; Syafri Anwar; nofrion dion (JURUSAN GEOGRAFI FIS UNP, 2017)
The purpose of the research to determine the effect of the application of active learning type of Hollywood Squares using LKS to the results of learning geography students class XI IPS SMAN 1 Sutera Pesisir Selatan Regency. The hypothesis in this study is